Explaining the Level of Credit Spreads: Option-Implied Jump Risk Premia in a Firm Value Model - Cremers, K. J. Martijn; Driessen, Joost; Maenhout, Pascal (Review of Financial Studies, 2008)
[We study whether option-implied jump risk premia can explain the high observed level of credit spreads. We use a structural jump-diffusion firm value model to assess the level of credit spreads generated by option-implied jump risk premia. Prices and returns of equity index and individual options are used to estimate the jump parameters. We further calibrate the model to historical information on default risk and the equity premium. The results show that incorporating option-implied jump risk premia brings predicted credit spread levels much closer to observed levels. The introduction of jumps also helps to improve the fit of the volatility of credit spreads and equity returns.]